Preparation method of vacancy confinement tin monatomic doped bismuth nanosheet and application of vacancy confinement tin monatomic doped bismuth nanosheet in synthesis of ethanol
By preparing a vacant limited-domain tin single-atom doped bismuth nanosheet catalyst, the electroreduction pathway of CO2 is adjusted using the Sn-Bi dual-active site, the problem of insufficient selectivity and efficiency of CO2 reduction to ethanol in the prior art is solved, and the efficient and highly selective CO2 reduction to C2H5OH is achieved.
Patent Information
- Application Number
- CN202411755312.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve efficient and selective reduction of CO2 to ethanol (C2H5OH), which leads to slow reaction kinetics and diversified product distribution due to insufficient activity and selectivity of the catalyst.
By preparing a vacant limited-domain tin single-atom doped bismuth nanosheet (Sn-Bi nanosheet) catalyst, the electroreduction pathway of CO2 is adjusted using the Sn-Bi dual-active site to improve catalytic activity and selectivity.
High-efficiency electrocatalytic reduction of CO2 to C2H5OH, the Faraday efficiency of C2H5OH is as high as 28%, the partial current density is as high as 1.6mA cm-2, and the total Faraday efficiency of CO2 conversion is 86%, which significantly improves the selectivity and efficiency of the reaction.
Smart Images

Figure CN119710798A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical catalysis, and in particular to a preparation method of vacancy-confined tin single-atom doped bismuth nanosheets and an application of the nanosheets in electrocatalytic synthesis of ethanol. Background Art
[0002] The electrochemical CO2 reduction reaction (CO2RR) has attracted extensive attention due to its potential to produce valuable chemicals and fuels, and provides a promising route to simultaneously address environmental issues and meet the energy storage requirements of renewable energy. (Li, L.; Li, X.; Sun, Y.; Xie, Y. Rational design of electrocatalytic carbon dioxide reduction for a zero-carbon network. Chem. Soc. Rev. 2022, 51(4), 1234-1252. Masel, RI; Liu, Z.; Yang, H.; Kaczur, JJ; Carrillo, D.; Ren, S.; Salvatore, D.; Berlinguette, C. P. An industrial perspective on catalysts for low-temperature CO2 electrolysis. Nat. Nanotechnol. 2021, 16(2), 118-128.) However, CO2RR involves a complex process of multiple proton and electron transfers, which often leads to slow reaction kinetics and diverse product distributions. Therefore, there are a series of substantial difficulties in achieving efficient and selective CO2 conversion by rationally regulating competing pathways, so it is necessary to develop innovative catalysts that can direct the reaction to the desired product. (Bagchi, D.; Roy, S.; Sarma, SC; Peter, SC Toward unifying the mechanistic concepts in electrochemical CO2 reduction from an integrated material design and catalytic perspective. Adv. Funct. Mater. 2022, 32 (51), 2209023. Haaring, R.; Kang, PW; Guo, Z.; Lee, JW; Lee, H. Developing catalysts integrated in gas-diffusion electrodes for CO2electrolyzers. Acc. Chem. Res. 2023, 56 (19), 2595-2605.) However, highly selective and active catalysts are the biggest challenge for electrocatalytic reduction of CO2 to C2H5OH. Adjusting the product selectivity in CO2RR requires precise control of the reaction pathway and reaction kinetics.It is challenging to control the CO2RR pathway on the catalyst surface to obtain the desired product because, during the reaction, desorption, hydrogenation and intermediate coupling processes occur simultaneously and compete with each other, resulting in low product selectivity. If the reaction pathway can be accurately adjusted, the controllability of CO2RR and the economy of the entire electrolyzer system can be greatly improved. The present invention precisely controls the adsorption strength of the catalytic active sites to the product intermediates by screening the chemical composition and surface environment of the Bi-based catalyst and optimizing the catalyst preparation process, thereby adjusting the electro-reduction pathway of CO2, achieving high-performance electrocatalytic CO2 production of C2 products by Bi-based catalysts, and expanding the application of Bi-based catalysts in the field of CO2RR production of C2 products. Its production process is more environmentally friendly, more efficient, and more convenient to use, and has gradually become one of the focuses of extensive attention of many researchers in the field. Summary of the invention
[0003] In order to address the deficiencies of the prior art and cost considerations, the present invention provides an application of a vacancy-limited tin single atom doped bismuth nanosheet catalyst to reduce CO2 to C2H5OH. Due to the presence of the Sn-Bi dual active sites, CO2 is more easily adsorbed and activated on the surface of the Sn-Bi nanosheet than on the surface of the Bi nanosheet, allowing the reaction to proceed along the reaction path to generate the C2 product, thereby achieving the effect of controlling the formation of the intermediate required for the C2 product to catalyze the generation of C2H5OH. The material can reduce CO2 to C2H5OH under atmospheric conditions. The reaction system in this section is carried out in a 0.5M KHCO3 solution, with a reaction voltage of -0.2 to -1.0V (vs.RHE), and the main products are C2H5OH, CH3OH, HCOOH, and CH4. At -0.7V (vs.RHE), the Faraday efficiency of C2H5OH is as high as 28%, and the partial current density of C2H5OH is as high as 1.6mA cm -2 (The total Faraday efficiency of CO2 conversion is 86%). Sn-Bi nanosheets for efficient electrocatalytic reduction of CO2 provide a new direction for designing transition metal-based catalysts with high activity and high C2 product selectivity. This invention saves costs, turns waste into treasure, is simple to operate, and has good commercial value and application prospects.
[0004] The present invention achieves the above object through the following technical solutions:
[0005] The present invention provides a method for preparing vacancy-confined tin single-atom doped bismuth nanosheets, the method comprising the following steps:
[0006] Step 1, preparation of bismuth oxybromide: placing an alcohol solution in which bismuth is dissolved in a prepared bismuth nitrate solution, centrifuging at different speeds, and then washing several times to obtain BiOBr ultrathin nanosheets (VBi-BiOBr) with abundant Bi vacancies on the surface;
[0007] Step 2, preparation of tin-doped bismuth oxybromide nanosheets: VBi-BiOBr ultrathin nanosheets are uniformly dispersed in deionized water and placed on a stirring table for stirring, and then SnCl4 solution is slowly added dropwise during stirring, the reacted solution is centrifuged to obtain a precipitate, and then the precipitate is washed with alcohol and deionized water to obtain tin-doped bismuth oxybromide nanosheets (Sn-BiOBr nanosheets);
[0008] Step 3, preparation of vacancy confined tin single atom doped bismuth nanosheets: add tin-doped bismuth oxybromide nanosheets and Nafion solution into an ethanol-water mixed solution, add the mixed solution dropwise onto the surface of a carbon paper electrode, and dry naturally to prepare a Sn-Bi nanosheet modified carbon paper electrode. Apply a constant voltage of -1 V under a three-electrode system to obtain vacancy confined tin single atom doped bismuth nanosheets (Sn-Bi nanosheets).
[0009] Preferably, the specific steps for preparing bismuth oxybromide are as follows:
[0010] Step a: Mix 9 mL H2O, 1 mL CH3COOH, and 0.4850 g Bi(NO3)3·5H2O and stir evenly, referred to as solution A. Then dissolve 0.3873 g [C16-MIm]Br in 10 mL alcohol, referred to as solution B. Place the prepared solution A on a stirring table and stir continuously, and add solution B to solution A within 5 minutes;
[0011] Step b: After continuing to stir for 60 minutes, the mixture is centrifuged at a speed of about 1000 rpm, the suspension is taken to remove large-sized nanosheets, and the suspension is centrifuged at a rate of 12000 rpm. The obtained precipitate is washed several times with water and anhydrous ethanol to obtain BiOBr ultrathin nanosheets with abundant Bi vacancies on the surface.
[0012] Preferably, the specific steps for preparing tin-doped bismuth oxybromide nanosheets are as follows: 5 mg SnCl4 is added to 50 mL distilled water, ultrasonicated for 30 minutes to make it evenly dispersed, and the prepared BiOBr ultrathin nanosheets are evenly dispersed in 0.5 mg mL -1 The mixture was placed in deionized water and stirred on a stirring table to prepare a VBi-BiOBr solution, and then the prepared SnCl4 solution was slowly added dropwise to the VBi-BiOBr solution, and the solution was stirred for 12 hours at room temperature and pressure. The reacted solution was centrifuged to obtain a precipitate, and the precipitate was then washed with alcohol and deionized water to obtain tin-doped bismuth oxybromide nanosheets.
[0013] Preferably, the specific steps for preparing vacancy-confined tin single atom doped bismuth nanosheets are as follows: take 5 mg of tin-doped bismuth oxybromide nanosheets, and add them and 40 μL of Nafion solution with a mass ratio of 5% to 1 mL of ethanol-water mixed solution with a volume ratio of 3:1, ultrasonicate for 30 minutes to form a mixed solution, take 20 μL of the mixed solution and drop it on the surface of a carbon paper electrode with an area of 1 cm×1 cm, dry it naturally to make a Sn-Bi nanosheet modified carbon paper electrode, apply a constant voltage of -1 V (vs. RHE) to the electrode under a three-electrode system for 5 minutes, and you can get vacancy-confined tin single atom doped bismuth nanosheets.
[0014] An application of vacancy confined tin single atom doped bismuth nanosheets, wherein an electrode made of vacancy confined tin single atom doped bismuth nanosheets is placed in an H-type electrolytic cell containing 0.5M KHCO3 electrolyte solution, a voltage is applied to the working electrode through an electrochemical workstation, and high-purity CO2 is continuously introduced into the cathode chamber, the reaction voltage is -0.2 to -1.0V (vs.RHE), and the main products are C2H5OH, CH3OH, HCOOH, and CH4H.
[0015] Preferably, at -0.7 V (vs. RHE), the Faradaic efficiency of C2H5OH is as high as 28%, and the partial current density of C2H5OH is as high as 1.6 mA cm -2 , the overall Faradaic efficiency of CO2 conversion is 86%.
[0016] Preferably, the electrochemical reduction of carbon dioxide to synthesize carbon-containing products is carried out at normal temperature and pressure.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] 1. Sn single atom doped Bi nanosheets, namely Sn-Bi nanosheets, were prepared by an in-situ electro-reduction method.
[0019] 2. The Sn-Bi dual active sites on Sn-Bi nanosheets are easier to adsorb and activate CO2 than on Bi nanosheets, allowing the reaction to proceed selectively toward the C2 reaction pathway, thereby catalyzing the conversion of CO2 into C2H5OH.
[0020] 3. Sn-Bi nanosheets are not only active and selective for CO2RR, but also highly stable. After Sn-Bi nanosheets were subjected to -0.7V for 60 hours, the Faradaic efficiency of C2H5OH was still 80% of the highest value.
[0021] 4. The present invention, through screening the chemical composition and surface environment of Bi-based catalysts and optimizing the catalyst preparation process, precisely controls the adsorption strength of the catalytic active sites to the product intermediates, thereby adjusting the CO2 electroreduction pathway, achieving high-performance electrocatalytic CO2 production of C2 products by Bi-based catalysts, and expanding the application of Bi-based catalysts in the field of CO2RR production of C2 products. Its production process is more environmentally friendly, more efficient, and more convenient to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The specific embodiments of the present invention are further described in detail below with reference to the accompanying drawings, wherein:
[0023] Figure 1 (a) (b) HRTEM images of Sn-Bi nanosheets and (b) VBi-BiOBr, respectively.
[0024] Figure 2 (a) (b) are TEM and STEM-HAADF images of Sn-Bi nanosheets, respectively.
[0025] Figure 3 EPR images of VBi-BiOBr and Sn-Bi nanosheets.
[0026] Figure 4 (a) XRD patterns of Sn-Bi nanosheets and VBi-BiOBr, (b) Sn K-edge k3-weighted EXAFS Fourier transform R-space spectra of SnO2, Sn foil and Sn-Bi nanosheets, (c) normalized Sn K-edge XANES spectra of SnO2, Sn foil and Sn-Bi nanosheets.
[0027] Figure 5 Linear scanning curves of Sn-Bi nanosheets in saturated CO2 and saturated Ar atmospheres.
[0028] Figure 6 (a) and (b) are the Faraday efficiencies of the catalytic products of VBi-BiOBr and Sn-Bi nanosheets in different potential ranges under a continuous and stable CO2 atmosphere.
[0029] Figure 7 The change of reduction current with time and the Faraday efficiency of C2H5OH during the continuous electrochemical CO2RR catalysis of Sn-Bi nanosheets. DETAILED DESCRIPTION
[0030] The embodiments of the present invention are described in detail below with reference to the accompanying drawings:
[0031] Embodiment 1:
[0032] A method for preparing vacancy-confined Sn single-atom doped bismuth nanosheets from BiOBr ultrathin nanosheets (VBi-BiOBr) with abundant Bi vacancies on the surface.
[0033] Step 1, preparation of bismuth oxybromide: placing an alcohol solution in which bismuth is dissolved in a prepared bismuth nitrate solution, centrifuging at different speeds, and then washing several times to obtain BiOBr ultrathin nanosheets with abundant Bi vacancies on the surface;
[0034] The preparation concrete steps of bismuth oxybromide are as follows:
[0035] Step a: Mix 9 mL H2O, 1 mL CH3COOH, and 0.4850 g Bi(NO3)3·5H2O and stir evenly, referred to as solution A. Then dissolve 0.3873 g [C16-MIm]Br in 10 mL alcohol, referred to as solution B. Place the prepared solution A on a stirring table and stir continuously, and add solution B to solution A within 5 minutes;
[0036] Step b: After continuing to stir for 60 minutes, the mixture is centrifuged at a speed of about 1000 rpm, the suspension is taken to remove large-sized nanosheets, and the suspension is centrifuged at a rate of 12000 rpm. The obtained precipitate is washed several times with water and anhydrous ethanol to obtain BiOBr ultrathin nanosheets (VBi-BiOBr) with abundant Bi vacancies on the surface.
[0037] Step 2, preparation of tin-doped bismuth oxybromide nanosheets: VBi-BiOBr ultrathin nanosheets are uniformly dispersed in deionized water and placed on a stirring table for stirring, and then SnCl4 solution is slowly added dropwise during stirring, the reacted solution is centrifuged to obtain a precipitate, and then the precipitate is washed with alcohol and deionized water to obtain tin-doped bismuth oxybromide nanosheets (Sn-BiOBr nanosheets);
[0038] The specific steps for preparing tin-doped bismuth oxybromide nanosheets are as follows: 5 mg SnCl4 was added to 50 mL distilled water and ultrasonicated for 30 minutes to make it evenly dispersed. The prepared BiOBr ultrathin nanosheets were evenly dispersed in 0.5 mg mL -1 The mixture was placed in deionized water and stirred on a stirring table to prepare a VBi-BiOBr solution, and then the prepared SnCl4 solution was slowly added dropwise to the VBi-BiOBr solution, and the solution was stirred for 12 hours at room temperature and pressure. The reacted solution was centrifuged to obtain a precipitate, and the precipitate was then washed with alcohol and deionized water to obtain tin-doped bismuth oxybromide nanosheets.
[0039] Step 3, preparation of vacancy confined tin single atom doped bismuth nanosheets: add tin-doped bismuth oxybromide nanosheets and Nafion solution into an ethanol-water mixed solution, add the mixed solution dropwise onto the surface of a carbon paper electrode, and dry naturally to prepare a Sn-BiOBr nanosheet modified carbon paper electrode. Apply a constant voltage of -1 V under a three-electrode system to obtain vacancy confined tin single atom doped bismuth nanosheets.
[0040] The specific steps for preparing vacancy-confined tin single atom doped bismuth nanosheets are as follows: take 5 mg of tin-doped bismuth oxybromide nanosheets, and add them and 40 μL of 5% Nafion solution by mass into 1 mL of ethanol-water mixed solution with a volume ratio of 3:1, ultrasonicate for 30 minutes to form a mixed solution, take 20 μL of the mixed solution and drop it on the surface of a carbon paper electrode with an area of 1 cm×1 cm, dry it naturally to make a Sn-Bi nanosheet modified carbon paper electrode, apply a constant voltage of -1 V (vs. RHE) to the electrode under a three-electrode system for 5 minutes, and you can get vacancy-confined tin single atom doped bismuth nanosheets.
[0041] This paper conducts phase characterization analysis on Sn-Bi(012) and Bi(012) nanosheets to confirm their morphological and structural characteristics. Figure 1 and Figure 2 It can be confirmed that Sn-Bi(012) is in nanosheet structure. At the same time, HRTEM image results ( Figure 1 a and Figure 1 b) shows high-resolution lattice fringes, which correspond to 0.282nm for the BiOBr (102) surface and 0.328nm for the Sn-Bi nanosheet (012) surface, respectively, indicating that the two materials have good crystallinity. In addition, it can be observed that some Bi atoms are missing from the surfaces of the two ultra-thin nanosheets, indicating the presence of a small amount of Bi vacancies. High-Angle Annular Dark Field (HAADF-STEM) image ( Figure 2 b) It is clearly shown that Sn atoms are anchored on the Bi nanosheets.
[0042] Electron paramagnetic resonance spectroscopy (EPR) Figure 3 As shown in Figure 2, it can be observed that the EPR curve of the Sn-Bi nanosheet has an obvious signal peak at g = 2.0038, which indicates the existence of vacancy defects in the Sn-Bi nanosheet. Figure 4 a) Further investigation of the chemical composition of the material revealed that there was no peak of Sn nanoparticles in the XRD spectrum of the Sn-Bi nanosheets, and the crystallinity was good, which further indicated that Sn did not exist in the Sn-Bi nanosheets in the form of a single substance. Figure 4b is the Fourier transform diagram of the EXAFS curve. It can be seen that there are Sn-O bonds and Sn-Bi bonds in the Sn-Bi nanosheets. Through fitting, we have further determined the atomic pairing mode in Sn-Bi. Figure 4 c shows the k-edge XANES analysis results of Sn. The near edges of Sn foil, Sn-Bi nanosheets, and SnO2 shift to the right in turn, which indicates that the valence of Sn in Sn-Bi nanosheets is between Sn(0) and Sn(4+), indicating that the valence state of Sn decreases after the reduction voltage applied during the preparation process.
[0043] Embodiment 2:
[0044] An application of vacancy confined tin single atom doped bismuth nanosheets, wherein an electrode made of vacancy confined tin single atom doped bismuth nanosheets is placed in an H-type electrolytic cell containing 0.5M KHCO3 electrolyte solution, a voltage is applied to the working electrode through an electrochemical workstation, and high-purity CO2 is continuously introduced into the cathode chamber, the reaction voltage is -0.2 to -1.0V (vs.RHE), and the main products are C2H5OH, CH3OH, HCOOH, and CH4H.
[0045] Among them, at -0.7 V (vs. RHE), the Faradaic efficiency of C2H5OH is as high as 28%, and the partial current density of C2H5OH is as high as 1.6 mA cm -2 , the overall Faradaic efficiency of CO2 conversion is 86%.
[0046] Among them, the electrochemical reduction of carbon dioxide to synthesize carbon-containing products is carried out at normal temperature and pressure.
[0047] This paper uses an H-type electrolytic cell to perform CO2RR tests on the catalyst in saturated Ar and saturated CO2 atmospheres in an electrolyte environment of 0.5M KHCO3. LSV curve ( Figure 5 ) showed that when the potential was greater than -0.5 V (vs. RHE), the Sn-Bi nanosheets exhibited a significantly higher current density in CO2-saturated electrolyte than in Ar-saturated electrolyte, which indicates that the catalyst reacted violently in a saturated CO2 environment and had a strong catalytic activity for CO2.
[0048] In order to further confirm the Sn-Bi nanosheets and V Bi -BiOBr's catalytic performance and confirmation of its catalytic products. This paper further conducts quantitative analysis of the products to confirm the selectivity of the two catalysts. Figure (6a, b) is Sn-Bi nanosheets and V Bi -BiOBr in a continuous and stable CO2 atmosphere, the Faradaic efficiency of the products in each potential range. The Faradaic efficiency of all products was analyzed by gas chromatography and 1H NMR was calculated after quantitative calculation and analysis. It can be seen that at a voltage of -0.5V to -0.9V (vs. RHE), Sn-Bi nanosheets can catalyze CO2 into C2H5OH, CH4, C2H4, CO, HCOOH, and a small amount of by-product H2. It is also worth noting that at -0.6V (vs. RHE), 1 H NMR detected the presence of C2H5OH and the Faraday efficiency of C2H5OH, which was consistent with the results of mass spectrometry and confirmed each other. In addition, the Faraday efficiency of Sn-Bi nanosheets reached the highest at -0.7V (vs. RHE), which was 28%. On the Bi nanosheet catalyst with abundant Bi vacancies on the surface, only HCOOH, CO and the byproduct H2 were detected.
[0049] Sn-Bi nanosheets are not only active and selective for ECO2RR, but also highly stable. Figure 7 It can be seen that after Sn-Bi nanosheets were subjected to -0.7 V for 60 hours, the Faradaic efficiency of C2H5OH was still 80% of the highest value.
[0050] In summary, the vacancy-confined tin single atom-doped bismuth nanosheet catalyst prepared by the method of the present invention can be used as an electrocatalyst with good performance, and can achieve high selectivity and high Faraday efficiency for electrocatalytic reduction of CO2 to synthesize C2H5OH at room temperature and pressure. The present invention shows that under the optimal conditions, the Faraday efficiency of C2H5OH of the vacancy-confined tin single atom-doped bismuth nanosheet catalyst is as high as 28%, and the partial current density of C2H5OH is as high as 1.6 mA cm -2 (The total Faraday efficiency of CO2 conversion is 86%). This result shows that the vacancy-confined tin single atom doped bismuth nanosheet catalyst for CO2 reduction has good commercial value and application.
[0051] The above are only preferred embodiments of the present invention. It should be pointed out that for ordinary technicians in this technical field, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the technical principles of the present invention. These changes, modifications, substitutions and variations should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing vacancy-confined tin single-atom doped bismuth nanosheets, characterized in that: The Method The steps include: Step 1, preparation of bismuth oxybromide (BiOBr): placing an alcohol solution in which bismuth is dissolved in a prepared bismuth nitrate solution, centrifuging at different speeds, and then washing several times to obtain BiOBr ultrathin nanosheets (VBi-BiOBr) with abundant Bi vacancies on the surface; Step 2, preparation of tin-doped bismuth oxybromide nanosheets: VBi-BiOBr ultrathin nanosheets are uniformly dispersed in deionized water and placed on a stirring table for stirring, and then SnCl4 solution is slowly added dropwise during stirring, the reacted solution is centrifuged to obtain a precipitate, and then the precipitate is washed with ethanol and deionized water to obtain tin-doped bismuth oxybromide nanosheets; Step three, preparation of vacancy confined tin single atom doped bismuth (Sn-Bi) nanosheets: add tin-doped bismuth oxybromide nanosheets and Nafion solution into an ethanol-water mixed solution, add the mixed solution dropwise onto the surface of a carbon paper electrode, and dry naturally to prepare a Sn-Bi nanosheet modified carbon paper electrode. Apply a constant voltage of -1 V in a three-electrode system to obtain vacancy confined tin single atom doped bismuth nanosheets.
2. The method for preparing vacancy-confined tin single-atom doped bismuth nanosheets according to claim 1, characterized in that: The preparation concrete steps of bismuth oxybromide are as follows: Step a: Mix 9 mL H2O, 1 mL CH3COOH, and 0.4850 g Bi(NO3)3·5H2O and stir evenly, referred to as solution A. Then dissolve 0.3873 g [C16-MIm]Br in 10 mL alcohol, referred to as solution B. Place the prepared solution A on a stirring table and stir continuously, and add solution B to solution A within 5 minutes; Step b: After continuing to stir for 60 minutes, the mixture is centrifuged at a speed of about 1000 rpm, the suspension is taken to remove large-sized nanosheets, and the suspension is centrifuged at a rate of 12000 rpm. The obtained precipitate is washed several times with water and anhydrous ethanol to obtain BiOBr ultrathin nanosheets with abundant Bi vacancies on the surface.
3. The method for preparing vacancy-confined tin single-atom doped bismuth nanosheets according to claim 1, characterized in that: The specific steps for preparing tin-doped bismuth oxybromide nanosheets are as follows: 5 mg SnCl4 was added to 50 mL distilled water and ultrasonicated for 30 minutes to make it evenly dispersed. The prepared BiOBr ultrathin nanosheets were evenly dispersed in 0.5 mg mL -1 The mixture was placed in deionized water and stirred on a stirring table to prepare a VBi-BiOBr solution, and then the prepared SnCl4 solution was slowly added dropwise to the VBi-BiOBr solution, and the solution was stirred for 12 hours at room temperature and pressure. The reacted solution was centrifuged to obtain a precipitate, and the precipitate was then washed with alcohol and deionized water to obtain tin-doped bismuth oxybromide nanosheets.
4. The method for preparing vacancy-confined tin single-atom doped bismuth nanosheets according to claim 1, characterized in that: The specific steps for preparing vacancy-confined tin single atom doped bismuth nanosheets are as follows: take 5 mg of tin-doped bismuth oxybromide nanosheets, and add them and 40 μL of 5% Nafion solution by mass into 1 mL of ethanol-water mixed solution with a volume ratio of 3:1, ultrasonicate for 30 minutes to form a mixed solution, take 20 μL of the mixed solution and drop it on the surface of a carbon paper electrode with an area of 1 cm×1 cm, dry it naturally to make a Sn-BiOBr nanosheet modified carbon paper electrode, apply a constant voltage of -1 V (vs. RHE) to the electrode under a three-electrode system for 5 minutes, and you can get vacancy-confined tin single atom doped bismuth nanosheets.
5. An application of vacancy-confined tin single atom doped bismuth nanosheets, characterized in that: An electrode made of vacancy-confined tin single atoms doped with bismuth nanosheets was placed in an H-type electrolytic cell containing 0.5M KHCO3 electrolyte solution. A voltage was applied to the working electrode through an electrochemical workstation, and high-purity CO2 was continuously passed into the cathode chamber. The reaction voltage was -0.2 to -1.0 V (vs. RHE), and the main products were C2H5OH, CH3OH, HCOOH, and CH4.
6. The use of vacancy-confined tin single atom doped bismuth nanosheets according to claim 5, characterized in that: At -0.7 V (vs. RHE), the Faradaic efficiency of C2H5OH is as high as 28%, and the partial current density of C2H5OH is as high as 1.6 mA cm -2 , the overall Faradaic efficiency of CO2 conversion is 86%.
7. The use of vacancy-confined tin single atom doped bismuth nanosheets according to claim 5, characterized in that: The electrochemical reduction of carbon dioxide to synthesize carbon-containing products is carried out at room temperature and pressure.